Christian revival in the Presbyterian Church of Thailand between 1900 and 1941 : an ecclesiological analysis and evaluation - Son, Seung Ho (Stellenbosch : Stellenbosch University, 2011)
Thesis (DTh)--Stellenbosch University, 2003.